The altitude dependence of magnetic remanence in the slowly-cooled Precambrian plutonic terrain of West Greenland (Dataset) ... - J PIPER (Magnetics Information Consortium (MagIC), 2006)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: The altitude dependence of magnetic remanence in the slowly-cooled Precambrian plutonic terrain of West Greenland ...